How Financial Performance Influence Stock Return? The Role of Earning Per Share - Safa Aulia; Lenni Yovita; Herry Subagyo; Suhita Whini Setyahuni (Finance : International Journal of Management Finance, 2024)
The purpose of this study was to determine the effect of CR, DER, and ROE on Stock Returns with EPS as an intervening variable in LQ45 companies for the period 2020-2023. Quantitative methods are applied in this study. The population used is companies that have been included in the LQ45 index for the period 2020-2023 so that the sample obtained is 208 sample data processed by purposive sampling technique. The data were analysis using descriptive analysis, classical assumption test, path analysis, and sobel test using SPSS 21 software. Research findings in equation 1 (EPS) show the results that CR has a negative effect on EPS, DER has no effect on EPS, and ROE has a positive effect on EPS. While in equation 2 (Stock Return) shows the results that CR, DER, and EPS have a negative effect on Stock Return and ROE has no effect on Stock Return. The results of path analysis explain that EPS can mediate CR on Stock Returns. Meanwhile, EPS cannot mediate DER and ROE on Stock Returns.